What Will Be The Productivity Of Employees With Shorter Work Hours? - Cvetkoska, Violeta; Dimovska, Milanka (Computer Science Journals, 2021)
We live in a world where we struggle every day to strike a balance between private and professional life. Shortening working hours leads to higher productivity, but what prevents us from achieving perfect balance? The aim of this paper is to examine the problems, causes and changes that may affect the change of working hours, and to answer whether there is a real possibility of introducing shorter working hours than eight hours, while achieving maximum productivity. The research was conducted through four rounds of questionnaires using the method of qualitative forecasting - Delphi. The questionnaires were answered by 11 respondents from one financial institution in North Macedonia in the period between February 20 and May 24, 2019. For each round of the Delphi method the answers were obtained and served as an auxiliary tool for forming the next survey questionnaire. With the results of the last round the successful application of the method was confirmed by achieving consensus among our panel of experts. Although we concluded that there are no conditions for introducing a shorter working day than eight hours, still the respondents believe that by introducing certain changes they could perform the work tasks in a shorter period of time.
Keywords: Qualitative Prediction, Delphi Method, Working Hours, Productivity, Stress.